2012
DOI: 10.1088/0964-1726/22/2/025009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of epoxy-bonded iron–gallium particulate composites

Abstract: This paper presents the production process and the results of investigations into the microstructure and magnetic properties of epoxy-bonded iron–gallium (Galfenol) particulate composites. The manufactured composites consist of powdered Fe80Ga20 alloy particles of three different size distributions (ranging from 20 to 200 μm), bonded in an epoxy matrix with a filling factor of 0.80. The filling factor is defined as the ratio of the volume of Fe–Ga powder to the total volume of the composite’s constituents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…14 Comparison of magnetostriction as a function of Galfenol vol% for various magnetostrictive particulate composites available in literature. 23,31,[41][42][43][81][82][83][84][85][86] All results are for a 170 kA m À1 applied field. ME Terfenol-D results were calculated from reported ME coupling and piezoelectric coefficients at the same 170 kA m À1 applied field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Comparison of magnetostriction as a function of Galfenol vol% for various magnetostrictive particulate composites available in literature. 23,31,[41][42][43][81][82][83][84][85][86] All results are for a 170 kA m À1 applied field. ME Terfenol-D results were calculated from reported ME coupling and piezoelectric coefficients at the same 170 kA m À1 applied field.…”
Section: Discussionmentioning
confidence: 99%
“…ME Terfenol-D results were calculated from reported ME coupling and piezoelectric coefficients at the same 170 kA m À1 applied field. 42 10.00 33.9 Epoxy/Galfenol 43 83.80 6.9 Epoxy/Terfenol-D 87 57.00 72.6 Epoxy/Terfenol-D 87 20.00 49.8 Epoxy/Terfenol-D 88 20.00 39.7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they are easier to manufacture to the required geometry than the above-mentioned giant magnetostrictive alloys. Previous studies on MPCs have reported Terfenol-D particles [26] and Galfenol particles [27] dispersed through an epoxy resin matrix (Terfenol-D/epoxy and Galfenol/epoxy composites, respectively), Fe-Co alloy particles dispersed through a polyurethane matrix (Fe-Co/PU composites) [28] and various others. Positive magnetostriction values of 1600, 360, and 70 ppm been reported in Terfenol-D/epoxy, Galfenol/epoxy, and Fe-Co/PU, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum magnetostrictive coefficient of the composite material reaches %70 ppm. Walters et al [5] used low-energy blade milling under a protective argon atmosphere to obtain three different particle-sized Fe 80 Ga 20 alloy powders then mixed with an epoxy binder, and the magnetostriction of the composite was found to be 360 ppm. Gaudet et al [6] used mechanical alloying method to prepare Fe-Ga-based powders and investigate the structure of powder.…”
Section: Introductionmentioning
confidence: 99%